Effect of protein and vitamin B deficiency on the morpho-quantitative aspects of the myenteric plexus of the descending colon of adult rats - Eduardo José de Almeida Araújo; Débora de Mello Gonçales Sant'Ana; Sônia Lucy Molinari; Marcílio Hubner de Miranda Neto (Arquivos de Neuro-Psiquiatria, 2003)
We carried out this work with the purpose of studying the effects of protein and vitamin B deficiency on the morphologic and quantitative aspects of the myenteric plexus of the descending colon of adult Rattus norvegicus. Twenty-eight rats were divided in two groups, one of them receiving chow with 22% protein level (control) and the other fed with chow having 8% protein level without vitamin B supplementation, during 120 days. Whole-mounts of the descending colon were prepared and stained with Giemsa, NADH-diaphorase and NADPH-diaphorase. The undernourished rats had a body weight 11.84% less than the control group. Relative to the controls, the experimental group had a colonic area 48% smaller, 51.9% less Giemsa-stained neurons, 28.3% less NADH-diaphorase positive neurons and 24.2% less NADPH-diaphorase positive neurons.